Relations between Parental Autonomy Support and Coercion with Children’s Total Difficulties - Gan, Su Wan; Yaacob, Siti Nor; Tan, Jo-Pei; Juhari, Rumaya (Makara Human Behavior Studies in Asia, 2020)
Child-rearing practices can either negatively or positively influence the psychosocial outcomes of their children. Negative psychological outcomes such as total difficulties can result in peer relationship problem, hyperactivity, emotional symptoms, and conduct problem among children. Thus, this study aims to examine the relations between parental autonomy support and coercion with total difficulties of children in Malaysia. As respondents of this study, a total of 502 children aged between 9 and 12 years were recruited using a multistage proportionate-to-size sampling technique. The descriptive analysis found that 8.4% of respondents experienced an abnormal level of total difficulties score that can result in mental disorder. The results indicated that children who perceived a higher level of autonomy support from parents experienced a lower level of total difficulties. In contrast, children who perceived their parents as coercive reported more total difficulties. The results indicated that autonomy support from parents is vital in protecting their children during middle childhood from behavioral, emotional, and peer relationship difficulties. Parental coercion tends to intensify total difficulties. Thus, to help their children in mitigating the performance of total difficulties, parents should be empowered with positive parenting skills.